Microanatomic structure of cetacean skin in the urogenital region - Jones, Flynn Margaret (Virginia Tech, 1993)
It was hypothesized that there may be microanatomic specializations in the urogenital slit and mammary region of cetaceans. There may be an integumentary-linked mechanism in these animals similar to that which causes the milk let-down response in terrestrial mammals. This hypothesis was tested on tissue samples from fourteen animals collected in a standardized array of fourteen samples from the urogenital area, and one each from the ventral aspect of the flipper and the mid-dorsal body wall for comparison. Using standard histological and ultrastructural procedures, including both transmission and scanning electron microscopy, tissues from nine species were investigated. These included the bottlenose dolphin (Tursiops truncatus), striped dolphin (Stenella coeruleoalba), harbor porpoise (Phocoena phocoena), pygmy sperm whale (Kogia breviceps), short and long finned pilot whales (Globicephala macrorhynchus and malaena respectively), beluga whale (Delphinapterus leucas), humpback whale (Megaptera novaeangliae), and fin whale (Balaenoptera physalus). Measurements were taken of the height of the epidermis, the thickness of the epidermal stratum externum, and the height and number of dermal papillae. Co1lagen bundles of the reticular dermis were measured and ranked by diameter. Nervous structures were quantitatively evaluated by type and location. No differences were found in the epithelial, connective, or nervous tissue of the skin in this region that would imply an increased sensitivity in this area. However, an observed unique organization of the connective tissue may imply a functional difference in the skin of the urogenital region unrelated to the milk let-down phenomenon. Possible alternative mechanisms for the initiation of milk let-down in cetaceans are discussed, including myoepithelial cell contraction caused by urogenital bumping by calves, vocalization by calvest and tacto/acoustic stimulation of the urogenital area by the calf. Epidermal thickness and papillary height varied among animals of different ...